Effect of caps on interest rates in Peru - Walter Cuba; Eduardo Díaz (Graduate Institute of International and Development Studies, 2023)
We review the initial effects of the imposition of caps on interest rates in Peru's financial system. We developed a methodology that allows us to quantify the potential exclusion of clients. We found that financial institutions excluded close to 243 thousand clients from the financial system. Regarding consumer loans, the exclusion ratio was higher among debtors outside the capital city, under the age of 25. Additionally, the effect was smaller for married debtors. In the case of small and micro-business loans, the effect was higher for natural persons, the commerce sector, and firms in the capital city. In summary, the effects induced by caps on interest rates are concentrated among people with lower incomes and those with vulnerable firms. Additionally, these debtors typically had the highest interest rates and were the main clients of non-banking financial institutions.
Keywords: G21; G23; G28; K20; 330; Cap on interest rate; credit market; exclusion